Tingkat Pendidikan, Literasi Keuangan, Perencanaan Keuangan dan Lotus Of Control Terhadap Perilaku Keuangan Pelaku UMKM (Studi Kasus di UMKM Labuhanbatu) - Sarkawi, Sarkawi; Ritonga, Mulkan; Prayoga, Yudi (Universitas Labuhanbatu, 2024)
This inquire about points to analyze the impact of instruction level, monetary education, monetary arranging, and locus of control on the budgetary behavior of Small scale, Little and Medium Ventures (MSMEs). Great money related behavior is imperative for MSME players in overseeing their money related assets proficiently to attain trade maintainability and development. The investigate strategy employments a quantitative approach by dispersing surveys to MSMEs in Labuhanbatu. The information gotten was analyzed utilizing different relapse strategies to distinguish the degree to which each free variable impacts money related behavior. The investigate comes about appear that the level of instruction features a positive and noteworthy impact on the money related behavior of MSME players. Budgetary education has moreover been proven to have a noteworthy affect in expanding the capacity of MSMEs to form suitable monetary choices. Separated from that, great money related arranging plays an critical part in making more organized and centered money related behavior. At long last, a solid locus of control, specifically the conviction that one has control over one's possess monetary results, has too been appeared to create a positive commitment to superior money related behavior. The level of instruction, budgetary education, budgetary arranging and locus of control impact the money related behavior of MSMEs in Labuhanbatu by 0.852 or 85.52%, whereas the remaining 14.48% is affected by other variables not inspected in this inquire.